Development and validation of a monolingual glossary of terms used by cockfighters - Manzano, Dexter Lucas (Penerbit Universiti Kebangsaan Malaysia, 2018)
This research sought to develop a monolingual glossary of terms used by cockfighters. The lexical entries were gathered through observation and interview with the selected cockfighters. Results revealed that the glossary uncovers and enables development of the language of the cockfighters as a specific group of language users. The collection was found as an initial effort to document the language of a specific activity context that is assumed an additional contribution to the cockfighting lexicon. The glossary consists of 98 entries, of which 82 are simple words, and 16 are compound words. The majority of the terms that cockfighters used originated from the Tagalog and Spanish languages; others came from English, Latin, and other Philippine languages like Iluko, Visayan, Kapampangan, Ilonggo, Cebuano. Regarding lexical classifications, these were identified as nouns, adjectives, and verbs. Hence, the monolingual glossary of terms in Filipino is a documentation of the practical, acceptable, and commonly used terms of cockfighters. It is hoped that this study could preserve the language in cockfighting and contribute a glossary that may be used in the field of language and cultural studies.